Dış ticaret teşvik ve yardımların önemi: Turquality uygulaması - Akın, Afra İmge (My University, 2010)
Günümüz büyüyen ve gelişen ekonomik koşullarında istikrarlı ve ivmeli büyümeyi yakalamanın en büyük şartlarından biri dışa uyumlu bir ihracat politikası ve uluslar arası standartları yakalamaktan geçmektedir. Küreselleşme sonucu farklılıkların daha çok ortadan kalkarak birbirine entegre ekonomiler yoğun global dünyada devletlerin makro anlamdaki büyümeleri artık daha çok ekonomilerine yön veren büyük ve çok uluslu şirketlerin performansları da büyük etki katmaktadır. Ancak gelişmekte olan ekonomiler için uluslar arası rekabetle yarışabilmeleri ve standartlara uygun performans sergileyebilmeleri açısından devlet tarafından verilecek olan teşvikler ve yardımlar oldukça önem arz etmektedir. Türkiye’nin altmışlı yıllar ile beraber uygulamaya koyduğu Planlı Kalkınma Politikası tarihsel gelişim olarak bakıldığında ilk teşvikler olarak değerlendirilmektedir. Teşvik ve yardımlar günümüze kadar çeşitlenerek geniş bir yelpazede farklılaşmış ve birden fazla türdeki faaliyetlerde yürürlükte olmaya devam etmektedir. Bu bağlamda başarı için kalite ve istikrarın yanı sıra stratejik planlamanın ve ileriye dönük bir vizyonun sağlanması ilk adımdır. Bu çalışmada da faaliyet türlerine ve çeşitlerine göre teşvik ve yardımların yanısıra dünyanın devlet destekli ilk ve tek markalaşma olan Turquality projesi ele alınarak incelenmiş, faydaları ve beklentiler genel değerlendirme kapsamında araştırmaya dahil edilmiştir.

In the globalized circumstances of world’s growing economic conditions one of the most crucial issue to reach to the accelerated and stable growth is an integrated implementing regulation and to have the international qualifications in foreign trade. As a result of the phenomenon of globalization which provides the elimination of discrepancies between national economies by integration process of markets, businesses and regulations the world has confronted the importance of the performance of multinational companies that lead macroeconomics. However, for developing countries, it is needed a high effort in order to show off an adequate performance and to compete with developed countries and international competitive economical climate without government supports and incentives. In the beginning of sixties Turkey applied to four different Development Plans which can be assessed as the first historical steps for government supports. As of today they diversified and are now valid in many types with the differentiation in various operating and business activities which are approved by the government in accordance with the regulation of communiqués in government supports. In order to speak of the achievement it is needed to provide not only quality and stabilization but also strategic planning and a forward-looking vision for the first step of growth. Therefore in this study, the government supports and incentives are examined according to the types of operating and business activities. In addition to that Turquality, which is the first and unique brand programme supported by a government in the world, is analyzed and both the advantages and the expectations about the regarding programme are inquired with an authorized person and included within the study with an overall evaluation.
Keywords: Dış Ticaret; Teşvik Yardımı